2022
DOI: 10.1371/journal.pone.0272040
|View full text |Cite
|
Sign up to set email alerts
|

Online searches of children’s oseltamivir in public primary and specialized care: Detecting influenza outbreaks in Finland using dedicated databases for health care professionals

Abstract: Introduction Health care professionals working in primary and specialized care typically search for medical information from Internet sources. In Finland, Physician’s Databases are online portals aimed at professionals seeking medical information. As dosage errors may occur when prescribing medication to children, professionals’ need for reliable medical information has increased in public health care centers and hospitals. Influenza continues to be a public health threat, with young children at risk of develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The situations and solutions are usually unique. This current study brings novel knowledge into the field of medicine shortages, and the prior work [20][21][22][23][24] supports the findings that HCPs and citizens seek real-time information in the dedicated medical online databases. This information on searching auto-injectors on the internet can be used in detection of epinephrine shortages.…”
Section: Plos Onesupporting
confidence: 77%
See 2 more Smart Citations
“…The situations and solutions are usually unique. This current study brings novel knowledge into the field of medicine shortages, and the prior work [20][21][22][23][24] supports the findings that HCPs and citizens seek real-time information in the dedicated medical online databases. This information on searching auto-injectors on the internet can be used in detection of epinephrine shortages.…”
Section: Plos Onesupporting
confidence: 77%
“…The strength of this study was the representativeness of log data from PD and HL, as demonstrated in the previous studies of infectious diseases [20][21][22][23][24]. However, this study has several limitations.…”
Section: Strengths and Limitationsmentioning
confidence: 92%
See 1 more Smart Citation